Analisa Proses Punch Press Pada Pembuatan Grill Untuk Model Bus Evonext Hino R260 - Fajrin Koto; Reza Setiawan; Farradina Choria Suci; Boni Sena (Peneliti.net, 2022)
Calculating the parameters in an effective and efficient production process is a necessity in order to meet the quality demands of users and applicable standards. This study uses analytical methods to calculate the parameters in the process. There are several analysis results, the first is the clearance value is 0.075 mm. The maximum die diameter is 10.17 mm and the minimum diameter is 10.15mm. The cutting force required is 8731.8 kgf and the stripper force required is 873.18 kgf. So the total force required is 9604.98 kgf. In the end, the machine capacity needed to carry out the entire punch press process was 12486.474 N